Linezolid resistant Staphylococcus aureus - Gandham, Pavani (International Journal of Research in Medical Sciences, 2017)
Linezolid is the only antibiotic available as an oral formulation for resistant staphylococcal infections. It is effective in skin & soft tissue infections, nosocomial pneumonias including VAP, infective endocarditis and MRSA meningitis. It is also effective in the eradication of both nasal & throat colonization of MRSA. Its high bioavailability and post antibiotic effect, ease of switching to oral therapy during its use and the fact that it can be used in patients of all ages, also in patients with liver disease and poor kidney function and its increased effectiveness over glycopeptides makes this drug a precious drug in the treatment of resistant staphylococcal infections. Linezolid resistance in staphylococcus is defined as a linezolid MIC of ≥8 mg/L. Reported Linezolid resistance in India and elsewhere is 2-20%.There is clonal dissemination of Linezolid Resistant Staphylococcus aureus (LRSA) within or across health care settings which demands continuous surveillance to determine the emergent risk of resistance strains and to establish guidelines for appropriate use. Clinical laboratories should confirm any LRSA preferably by a second method, prior to using linezolid for serious infections. Effective surveillance, more judicious use of this antibiotic, avoiding linezolid usage for empiric therapy in hospital acquired staphylococcus infections, optimization of the pharmacological parameters of the antibiotics in specific clinical situation, decreasing bacterial load by timely surgical debridement or drainage of collections, use of combination therapies would prevent the emergence of resistance to linezolid in staphylococcus aureus.